2006
DOI: 10.1097/01.mpg.0000235974.67496.e6
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Efficacy and Pharmacokinetics of Peginterferon α2a (40 kd) in Children With Chronic Hepatitis C

Abstract: Chronic hepatitis C virus (HCV) infection in children is a problem affecting thousands of children worldwide. Although standard interferon (INF) has better efficacy in pediatric patients than in adults, results in children with genotype 1 are poor; response rates to combination treatment with standard INF and ribavirin are better but the treatment requires thrice-weekly injections. The improved antiviral efficacy of weekly pegylated interferons relative to standard interferons in adults with chronic HCV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 29 publications
4
40
0
4
Order By: Relevance
“…Standard IFN 3 MU/m 2 three times a week with ribavirin 15 mg/kg/day for 48 weeks yielded an SVR of 40% to 60% overall, and 70% to 100% in genotype 2 or 3 infection (79). PEG IFN-alpha-2a or -2b and ribavirin have been used in small numbers of HCV-infected children with SVR rates of 43% to 59% (higher in genotypes 2 and 3 than in genotypes 1 and 4) (80,81). Whether EVR can be used, as in adults, to stop therapy early in patients destined to be nonresponders is not clear.…”
Section: Hcv-hiv Coinfectionmentioning
confidence: 99%
“…Standard IFN 3 MU/m 2 three times a week with ribavirin 15 mg/kg/day for 48 weeks yielded an SVR of 40% to 60% overall, and 70% to 100% in genotype 2 or 3 infection (79). PEG IFN-alpha-2a or -2b and ribavirin have been used in small numbers of HCV-infected children with SVR rates of 43% to 59% (higher in genotypes 2 and 3 than in genotypes 1 and 4) (80,81). Whether EVR can be used, as in adults, to stop therapy early in patients destined to be nonresponders is not clear.…”
Section: Hcv-hiv Coinfectionmentioning
confidence: 99%
“…This is in accordance with the prolonged exposure and higher AUC values obtained using PEG-Intron (PEG-Intron; EPAR). Treatments with PEGylated proteins such as PEG-interferon ␣ 2a (40 kDa; Pegasys) and PEGylated asparaginase do not reveal any specific adverse events linked to the PEG moiety (Avramis et al, 2002;Schwarz et al, 2003).Overall, the acute or chronic administration of PEG with a range of molecular weights by a range of routes has not led to any major toxicities, and signs of toxicity that do occur are only apparent at high dose. In light of this information, PEG can be considered to have a toxicological profile of very low concern in animals.…”
mentioning
confidence: 96%
“…This is in accordance with the prolonged exposure and higher AUC values obtained using PEG-Intron (PEG-Intron; EPAR). Treatments with PEGylated proteins such as PEG-interferon ␣ 2a (40 kDa; Pegasys) and PEGylated asparaginase do not reveal any specific adverse events linked to the PEG moiety (Avramis et al, 2002;Schwarz et al, 2003).…”
Section: Toxicology Of Pegylated Molecules In Animalsmentioning
confidence: 99%
“…Ribavirin is cleared by the kidneys and causes a dose-related hemolysis that can be severe and life threatening in patients with renal diseases [1]. Another study of pediatric patients with chronic HCV showed the safety and efficacy of PEG-IFN a-2a, both as monotherapy and in combination with ribavirin [10]. In order to decrease the risk of side effects, our patient was started on PEG-IFN a-2a monotherapy.…”
Section: Discussionmentioning
confidence: 99%